The Relation Between Institutional Ownerships, Debt Policy, Dividend Policy And Company Performance In Terms Of Clarifying Agency Conflict Mechanism : Case Study At Manufacturing Companies Listed At The Indonesian Stock Exchange - Costa Cabral, Mateus Xavier Da; Laksamana, Arsono; Rahayu, Mudjilah (International Journal of Scientific Research and Management (IJSRM), 2018)
Companies that go public, in general, have been managed professionally that can be tailored to the consumers’ needs under applicable regulations. Management within a company's business entity involves an agency relationship. The purpose of this study is to examine: a) a reciprocal relationship between institutional ownership, debt policy, dividend policy and company performance of manufacturing companies of the Indonesian Stock Exchange, b) the influence of institutional ownership, debt policy, dividend policy on the company performance of the manufacturing companies of the Indonesian Stock Exchange.This type of research includes associative research with a quantitative approach. The samples of this research as many as 98 manufacturing companies listed at the Indonesian Stock Exchange of the period of 2006-2015 with the technique of determining purposive samplings. Data analysis technique used in this research is Granger Causality test.The results of this study are: a) there is no reciprocal relationship between institutional ownership and debt policy, b) there is no reciprocal relationship between institutional ownership with dividend policy, c) no reciprocal relationship between debt policy and dividend policy, d) there is no reciprocal relationship between institutional ownership and company performance; e) there is no reciprocal relationship between debt policy and company performance; f) there is no reciprocal relationship between dividend policy and company performance; g) institutional ownership has a positive and partially significant influence on company performance, h) debt policy has a positive and partially significant influence on company performance, and i) dividend policy has positive and partially significant influence to companies performance on manufacturing company listed at the Indonesian Stock Exchange